Money spider dietary choice in pre‐ and post‐harvest cereal crops using metabarcoding. (9th October 2020) - Cuff, Jordan P.; Drake, Lorna E.; Tercel, Maximillian P.T.G.; Stockdale, Jennifer E.; Orozco‐terWengel, Pablo; Bell, James R.; Vaughan, Ian P.; Müller, Carsten T.; Symondson, William O.C.
Abstract : Money spiders (Linyphiidae) are an important component of conservation biological control in cereal crops, but they rely on alternative prey when pests are not abundant, such as between cropping cycles. To optimally benefit from these generalist predators, prey choice dynamics must first be understood. Money spiders and their locally available prey were collected from cereal crops 2 weeks pre‐ and post‐harvest. Spider gut DNA was amplified with two novel metabarcoding primer pairs designed for spider dietary analysis, and sequenced. The combined general and spider‐exclusion primers successfully identified prey from 15 families in the guts of the 46 linyphiid spiders screened, whilst avoiding amplification of Erigone spp. The primers show promise for application to the diets of other spider families such as Agelenidae and Pholcidae. Distinct invertebrate communities were identified pre‐ and post‐harvest, and changes in spider diet and, to a lesser extent, prey choice reflected this. Spiders were found to consume one another more than expected, indicating their propensity towards intraguild predation, but also consumed common pest families. Changes in spider prey choice may redress prey community changes to maintain a consistent dietary intake. Consistent provision of alternative prey via permanent refugia should be considered to sustain effective conservation biocontrol. Abstract : Distinct invertebrate communities were identified pre‐ and post‐harvest, and changes in spider diet and prey preferences reflected this. Spider prey choice may redress prey community changes to maintain a consistent dietary intake. Consistent provision of alternative prey via permanent refugia could sustain effective conservation biocontrol. Spiders consumed one another more than expected, indicating their propensity towards intraguild predation, but they also consumed common agricultural pests.